Etched track detector methods for the identification of target nuclear fragments in cosmic radiation and accelerator proton beams. (January 2021) - Inozemtsev, K.O.; Kodaira, S.; Kusumoto, T.; Kitamura, H.; Strádi, A.; Szabó, J.; Ambrožová, I.; Shurshakov, V.A.
Abstract: In this article, two etched track detector methods for measuring short-range particles are presented and compared. The primary method employs observations of the evolution of the track geometry in intermittent etching, with the use of the appropriate track scanning procedures. The alternative method requires one-step etching and a specific analysis of the track parameters. Both methods proved to be effective in identifying target nuclear fragments amongst a high background from primary cosmic radiation. Additionally, the linear energy transfer (LET) spectrum of the target nuclear fragments, obtained onboard the International Space Station, was found to be consistent with the results from high-energy proton beams in ground-based experiments. Highlights: Two competing etched track detector methods for measuring short-range particles are presented and compared. The method employed observations of track geometry evolution can improve estimation of short-range particles dose by 21–27%. The simplified method resulted in twice as fast data acquisition, losing about 20% of short-range particle dose. The LET distribution of short-range cosmic particles was found consistent with results from high-energy proton beam.